Exiting the fossil world: The effects of fuel taxation in the UK - Lucas Bretschger; Elise Grieg (ETH Zurich, CER-ETH - Center of Economic Research, 2020)
Carbon taxes remain economists favoured policy tool to curb emissions, but are unpopular among segments of the populations. Theoretical and numerical work tends to show the effectiveness of carbon taxes, but ex-post empirical analyses are still rare. In this paper we attempt to bridge this gap. We construct a theoretical general equilibrium model with dirty and clean transportation to show the static and dynamic effects of a fuel tax on transportation and consumption by deriving closed-form solutions. We take the predictions of the model to data on the UK Fuel Tax Escalator, and estimate the impact of the tax on CO2 emissions, GDP, and transport behaviour. With a potential control pool of OECD countries, we use the synthetic control method to estimate the difference between the observed outcome in the UK and a synthetic counterfactual UK. We find that the tax has a large and significant impact on CO2 emissions from traffic, while there is no discernable impact on GDP or growth. We do not find large changes in driving behaviours, but the available evidence points to a possible switch to rail travel from road travel.
Keywords: Q43; O47; Q56; O41; 330; fuel tax; synthetic control method; climate policy; transport; level and growth effects